Digital Empowerment of the Innovation of Ideological and Political Education Methods - Guo Ling (SHS Web of Conferences)
Digital technology has significantly empowered ideological and political education. Digital ideological and political education is the requirement of reform and innovation of ideological and political education in the new era. It is not only the innovation in the instrumental sense, but also the renewal of the mode of thinking on the value level. In the digital era, ideological and political education plays a leading role in the field of ideology and politics, and it should make use of big data technology to enhance the cohesion and leadership of the mainstream ideology, to enhance the vividness of ideological and political education by adapting educational content and methods, and to gather the power of ideological and political education by taking digital technology as the basis, breaking through the limitations of time and space and the field, and realizing the collection and sharing of high-quality resources.